2018
DOI: 10.1002/fsn3.874
|View full text |Cite
|
Sign up to set email alerts
|

Formation of the oxidized flavor compounds at different heat treatment and changes in the oxidation stability of milk

Abstract: The oxidized flavor could affect the sensory acceptability of consumers. In this study, the oxidized flavor compound (OFC) in different heated milk was analyzed using the solid phase microextraction–gas chromatography–mass spectrometry (SPME–GC–MS). The concentration of OFC increased with increasing the intensity of heat treatment. The concentrations of heptanal, nonanal, 2‐heptanone, and 2‐nonanone in the heated milk samples were in the range of 1.88–5.51, 1.03–3.26, 6.89–88.04, and 1.46–12.78 μg/kg, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Food deriving from a cook-chill supply chain belongs to a special class of products for which a shelf-life enhancement would be desirable to reach as complicated to obtain. Freezing, heating or drying procedure procedures can result in significant changes to the organoleptic properties of foods [65,66]. In addition, the use of chemical additives is not very suitable because they may cause a sensory modification of the product and even if not, their presence could make the product less appealing considering today's most prevalent consumer sensitivity [67].…”
Section: Methods To Improve Food Shelf-lifementioning
confidence: 99%
“…Food deriving from a cook-chill supply chain belongs to a special class of products for which a shelf-life enhancement would be desirable to reach as complicated to obtain. Freezing, heating or drying procedure procedures can result in significant changes to the organoleptic properties of foods [65,66]. In addition, the use of chemical additives is not very suitable because they may cause a sensory modification of the product and even if not, their presence could make the product less appealing considering today's most prevalent consumer sensitivity [67].…”
Section: Methods To Improve Food Shelf-lifementioning
confidence: 99%
“…Additionally, decreased hexanal content (Table 2) also results in increased oxidative stability. Li et al, (2019b) reported the TBARS level of raw milk in the range 0.02-0.03 whereas TBARS value of milk that was exposed to light and protected from light was 0.92 ± 0.09 mg/kg and 0.59 ± 0.184 mg/kg, respectively (Van et al, 2005). In WM reconstituted (12%) from powder the TBARs value ranged between 0.044 to 0.221 (Li et al, 2019a).…”
Section: Tbars Valuementioning
confidence: 98%
“…Milk is not only a nutritionally rich food, with essential nutrients such as lactose, protein, fat, vitamins (vitamin A, vitamin E, vitamin C, and B vitamins) and minerals (calcium, iron, zinc, and potassium), but also has active nutrients such as lactoferrin, lactoglobulin and whey protein. Raw milk has a characteristic milky flavor [ 3 , 4 ], which makes it more attractive to consumers. Based on the literature, free fatty acids, especially free short-chain fatty acids (FSCFAs), are critical factors which affect the milk flavor [ 3 , 5 ], and increased FSCFAs are the responsible for the sourness of milk [ 6 ].…”
Section: Introductionmentioning
confidence: 99%